Implementation of Supply Chain Management to Improve the Performance of Cirebon Batik SMEs - Harjadi, Dikdik; Arraniri, Iqbal (The journal of contemporary issues in business and government, 2022)
Small and Medium Enterprises (SMEs) are growing rapidly in Indonesia, ideas emerge thanks to an innovation that can be a strength for companies to strengthen their market position. Today's business world continues to compete to create a variety of consumer needs that are getting higher and smarter in choosing their needs. Every effort will make every effort to improve productivity, efficiency, fast, easy service, and continue to create new innovations to remain ahead and survive in the market.The purpose of this study was to examine the effect of information sharing, cooperation, long term relationship, Supply Chain Management and Business Performance. The data was processed using Structural Equation Modeling (SEM) with the help of the Analysis of Moment Structure (AMOS) version 18.0 program.